Study Literature Review Implementation of PSAK 22 Challenges and Opportunities for Indonesian Companies - Winda Utami Br Siburian; Rahelsa Octaviana; Auna Syafitri; Sri Miranty Siregar; Abel Desiyanti Manik; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This research aims to analyze the impact of implementing PSAK 22 on companies in Indonesia. This study will identify the challenges companies face in implementing this new accounting standard, as well as opportunities that can be exploited to improve the quality of financial reporting. Through literature reviews and case studies, it is hoped that this research can contribute to understanding the complexity of business combination accounting in Indonesia and provide recommendations for companies in facing these changes. The result is in-depth analysis of case studies of companies that have implemented PSAK 22 can provide a clearer picture of the challenges and opportunities they face. Comparing the experience of implementing PSAK 22 in Indonesia with other countries can provide a broader perspective and inspire best practices.